Potret Organisasi Tarekat Indonesia dan Dinamikanya - Moh. Rosyid (UIN K.H. Abdurrahman Wahid Pekalongan, 2018)
The goal of this research was to briefly describe the dynamics of tarekat organizations in Indonesia since the establishment of Ahl al-Tariqah al-Mu'tabarah al-Indonesi (JATMI, 1957) and Jam'iyyah al-Thariqah al-Mu'tabarah al-Nahdliyah (JATMAN), 1979) in Java, which was followed by that of the Indonesian Tarekat Ulama Council in Solok, West Sumatra (2016). The method of the current research is a literature review using content analysis techniques. The main findings are threefold, with the first suggesting how the criteria for tarekat maturity are needed in the organization of the tarekat. The second finding shows that the Sufism organization (tarekat) of the JATMI Nusantara in 1957 was prompted by the Tarekat Qadiriyah wa Naqsyabandiyah (TQN). Meanwhile, the internal conflict among Jatmi's leaders set into motion the establishment of a new institution which has a similar movement mission, i.e., JATMAN in 20 Early Rabbi of 1337 H / 10 October 1985 AD in Tegalrejo, Magelang, Central Java. The third finding shows that the dynamics of the organization have colored the Ulama institutions in Indonesia.